2010
DOI: 10.1089/lap.2010.0029
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Effectiveness of Laparoscopic Total Extraperitoneal (TEP) Repair for Recurrent Inguinal Hernia After Open Hernioplasty

Abstract: Background: Many studies have reported that laparoscopic total extraperitoneal (TEP) repair for recurrent inguinal hernia after an open hernioplasy was safe and effective. This study was conducted to evaluate TEP repair for recurrent inguinal hernia through a retrospective analysis of our data. Materials and Methods: We performed a retrospective analysis of the medical records of patients who were scheduled for laparoscopic TEP repair from December 2000 to December 2008. A total of 1065 cases of laparoscopic T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Inguinal Hernia Subtype. A total of 21 studies covering 228 756 procedures in 227 041 persons evaluated the risk of recurrence in relation to the inguinal hernia subtype [9][10][11][12][13]16,29,31,32,37,39,[41][42][43][44]47,[49][50][51][52][53] Of those, 4 studies evaluating primary inguinal hernias were included in a meta-analysis evaluating the risk of recurrence of direct inguinal hernias (DIH) compared with indirect inguinal hernias (IIH), covering 36 971 procedures in 35 342 persons. 29,31,32,43 The reasons for not including more studies into the meta-analysis was not reporting relative risk estimates or analyzing re-recurrence after operations for recurrent inguinal hernias instead of primary inguinal hernias.…”
Section: Local Hernia Characteristics As Risk Factor For Recurrence After Inguinal Hernia Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Inguinal Hernia Subtype. A total of 21 studies covering 228 756 procedures in 227 041 persons evaluated the risk of recurrence in relation to the inguinal hernia subtype [9][10][11][12][13]16,29,31,32,37,39,[41][42][43][44]47,[49][50][51][52][53] Of those, 4 studies evaluating primary inguinal hernias were included in a meta-analysis evaluating the risk of recurrence of direct inguinal hernias (DIH) compared with indirect inguinal hernias (IIH), covering 36 971 procedures in 35 342 persons. 29,31,32,43 The reasons for not including more studies into the meta-analysis was not reporting relative risk estimates or analyzing re-recurrence after operations for recurrent inguinal hernias instead of primary inguinal hernias.…”
Section: Local Hernia Characteristics As Risk Factor For Recurrence After Inguinal Hernia Surgerymentioning
confidence: 99%
“…34 The remaining studies found the same tendency that primary operation for DIH resulted in higher risk of reoperation, but not significantly. 13,37,39,41,44,[49][50][51][52][53] No studies found indications that IIH resulted in higher risk of recurrence than DIH.…”
Section: Local Hernia Characteristics As Risk Factor For Recurrence After Inguinal Hernia Surgerymentioning
confidence: 99%
“…This goes with the findings of Choi. 22 Lau 23 reported that occurrence of direct recurrent hernia reflects an inadequate reinforcement of the posterior wall by suture herniorrhaphy in the initial repair, and technical error or tension on the repair were possible contributing factors. Several studies have suggested that the potential causes for indirect recurrence includes missed hernia, incomplete dissection or low ligation of the sac, as well as incomplete restoration of the internal ring.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after TEPP hernioplasty for the primary inguinal hernia has come down markedly to 0.1 to 0.5% in recent years. 25,26 However, some recent studies have reported even 0% recurrence rate after primary laparoscopic repair through the TEPP approach. [27][28][29] Present study also did not record any instance of hernia recurrence in the mean follow-up period of 33 months.…”
Section: Wjolsmentioning
confidence: 99%